The Impact of Effective Corporate Boards and Audit Committees on Attracting Foreign Ownership in Listed Companies in the Gulf Cooperation Council - Al-shamahi, Mohammed Gubran; Abdul Manaf, Kamarul Bahrain; Al-arussi, Ali Saleh (Macrothink Institute, 2017)
This study empirically examines the impact of effectiveness of both corporate boards and audit committee on foreign ownership in selected non-financial listed companies of the stock markets in Gulf Cooperation Council (GCC) countries.Contrary to previous studies, this study enters the firm size, leverage, exchange rate risks, inflation risks and economic growth as control variables. For the first time, it also includes the political risks’ variable as a control variable that may affect foreign ownership.In term of panel data regression analysis, the study was built on fixed effect model and conducted to the period of 2012-2015 for 143 non-financial listed companies on the GCC stock markets.Our results explain that foreign ownership is positively related to the effectiveness of both the boards of directors and the audit committees. Political risks and firm size are positively significant with foreign ownership, while the leverage is negatively related to foreign ownership.The implication of this study may help beneficiaries in making better policy decisions and provide guidance for corporate managers on the needs of foreign investors.